PERAN MEDIASI KREATIVITAS DAN SIKAP PROAKTIF DALAM PENGARUH KECERDASAN EMOSIONAL PADA INTENSI BERWIRAUSAHA - Sriyanto & Siti Almaidah (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
This study aims to obtain a description of the intension of entrepreneurship students of the College of Economics S1 Program in Surakarta. In addition, to examine and analyze the role of creative mediation and proactive attitudes in the influence of emotional intelligence on the intention of entrepreneurship students of the College of Economics S1 Program in Surakarta. The sample in this research is 150 students, sampling using convenience sampling technique. Data quality testing is done by validity and reliability test. While the data analysis used in this study is the classical assumption test, multiple linear regression, and path analysis. Based on data analysis, the result is as follows: (1) proved that emotional intelligence has a positive and significant influence to intention of entrepreneurship, (2) proved that emotional intelligence has a positive and significant influence to creativity, (3) proved that emotional intelligence has a positive and significant influence to proactive attitude, (4) proved that creativity has a positive and significant influence to intention of entrepreneurship, (5) proved that proactive attitude has a positive and significant influence to intention of entrepreneurship, (6) proved that emotional intelligence has a positive and significant influence to intention of entrepreneurship with creativity as a mediator variable, (7) proved that emotional intelligence has a positive and significant influence to intention of entrepreneurship with a proactive attitude as a mediator variable. Keywords: emotional intelligence, intention to entrepreneurship, creativity, proactive attitude, path analysis